Author Correction: Larger mammals have longer faces because of size-related constraints on skull form. Issue 1 (December 2018) - Cardini, Andrea; Polly, P.
In Table 1 of this article, the descriptions of landmarks 14, 15, and 36 are incorrect. Landmarks 14 and 36 should read "Posterior extremity of occipital condyle along margin of foramen magnum" and landmark 15 should read "Opisthion". A correct version of Table 2 appears in the Author Correction associated with this article; the error has not been fixed in the original article.